2006
DOI: 10.1103/physrevlett.97.258001
|View full text |Cite
|
Sign up to set email alerts
|

Critical Scaling in Linear Response of Frictionless Granular Packings near Jamming

Abstract: We study the origin of the scaling behavior in frictionless granular media above the jamming transition by analyzing their linear response. The response to local forcing is non-self-averaging and fluctuates over a length scale that diverges at the jamming transition. The response to global forcing becomes increasingly nonaffine near the jamming transition. This is due to the proximity of floppy modes, the influence of which we characterize by the local linear response. We show that the local response also gove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
338
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(366 citation statements)
references
References 26 publications
(65 reference statements)
26
338
2
Order By: Relevance
“…In line with the arguments given above, it has been found that near the jamming point, one needs to coarse grain over the scale ℓ * to see elastic response emerge [26,27]: as one approaches the jamming point, one has to coarse grain over larger and larger lengths, diverging as ℓ * ∼ 1/∆Z. That elasticity emerges in granular media on long enough scales is also implicitly confirmed by the data of Fig.…”
Section: Behavior or Elastic Constants Near Jammingsupporting
confidence: 68%
See 4 more Smart Citations
“…In line with the arguments given above, it has been found that near the jamming point, one needs to coarse grain over the scale ℓ * to see elastic response emerge [26,27]: as one approaches the jamming point, one has to coarse grain over larger and larger lengths, diverging as ℓ * ∼ 1/∆Z. That elasticity emerges in granular media on long enough scales is also implicitly confirmed by the data of Fig.…”
Section: Behavior or Elastic Constants Near Jammingsupporting
confidence: 68%
“…1.7, which summarizes data for B and G for packings of two-dimensional discs interacting with Hertzian forces [26,27]. The bulk modulus B is clearly seen to scale as p 1/3 [5], which as we argued above is the scaling of the average bond strength for this force law.…”
Section: Behavior or Elastic Constants Near Jammingmentioning
confidence: 94%
See 3 more Smart Citations